Peningkatan Hasil Belajar Pendidikan Agama Katolik Melalui Model Pembelajaran Berbasis Masalah pada Materi Konsekuensi Pewartaan Yesus di Kelas VIII SMP Regina Pacis Surakarta - Winda Puspita Sari (Sekolah Tinggi Pastoral Kateketik (STPKat) Santo Fransiskus Assisi Semarang, 2024)
This research aims to improve the learning outcomes of grade VIII students in Catholic Religious Education on the material Consequences of the Proclamation of Jesus at Regina Pacis Junior High School Surakarta by applying the Problem-Based Learning model. Student learning outcomes in this material show low results due to conventional teaching methods. This Classroom Action Research (PTK) is carried out in two cycles involving planning, action, observation, and reflection stages. The results showed a significant increase in the average student score from cycle I to cycle II. The application of the PBL model also increases student involvement in the learning process, group work, and critical thinking skills.